Pulmonary arterial hypertension associated with connective tissue disease: meta-analysis of clinical trials. Issue 8 (1st August 2013) - Kuwana, Masataka; Watanabe, Hiroshi; Matsuoka, Nobushige; Sugiyama, Naonobu
Abstract : Objectives: Few studies have focused on pulmonary arterial hypertension (PAH) associated with connective tissue diseases (CTDs). The optimal treatment for CTD-PAH has yet to be established. Design: Meta-analysis of the data from evaluations of treatment for PAH generally (19 studies) and CTD-PAH specifically (nine studies) to compare the effects of pulmonary vasodilative PAH agents. MEDLINE, EMBASE and BIOSIS were searched. English-language full-text articles published between January 1990 and August 2012 were eligible. Setting: International. Participants: Patients with PAH generally (n=3073) and CTD-PAH specifically (n=678). Primary outcome measure: Exercise capacity (6 min walk distance, 6 MWD). Results: Patients with PAH (all forms) had mean age 32–55 years (women, 61–87%); CTD-PAH patients had mean age 45–55 years (women, 74–95%). Overall estimate of mean change in 6 MWD from baseline (95% CI) for the active treatment group versus the control group in all patients with PAH was 34.6 m (27.4–41.9 m). Pooled mean differences from the results for patients receiving placebo by subgroup of patients receiving phosphodiesterase (PDE)-5 inhibitors, endothelin receptor antagonists (ERAs) and prostacyclin (PGI2 ) analogues were 22.4–45.5, 39.5–44.2 and 12.4–64.9 m, respectively. Overall estimate of mean difference between changes in 6 MWD in patients with CTD-PAH was 34.2 m (23.3–45.0 m). Pooled mean differences by subgroup of patients receiving PDE-5 inhibitors, ERAs and PGI2 analogues in patients with CTD-PAH were 37.0–47.1, 14.1–21.7 and 21.0–108.0 m, respectively. ERAs were less effective in patients with CTD-PAH than all-form patients with PAH: 14.1 m (−4.4–32.6 m) vs 39.5 m (19.5–59.6 m) for bosentan and 21.7 m (2.2–41.3 m) vs 44.2 m (30.2–58.2 m) for ambrisentan. Conclusions: All three types of PAH agent are effective. However, ERAs may be a less effective choice against CTD-PAH; further studies are needed. Limitations include the limited number of studies for some agents and for patients with CTD-PAH.